Study The Effect of Different levels of Deficit Irrigation on the Productivity and Water Use Efficiency of Potatoes (Solanum Tuberosum.L) Variety. Everest (Damascus University Journal of agriculture sciences, 2025)
This research was conducted in AL-derkhabia in countryside rural Damascus during the season 2021, and the Potato tubers was planted on 8 April, 2021(Summer season), to study the possibility of improving the water use efficiency of Potatoes crop (Everest variety) by applying Deficit Irrigation. The experiment was designed by simple random design with five treatments of different amounts of water during plant growth stages in three replications for each treatment on the level of confidence 95% . The treatments were as follows: Full irrigation treatment FI (control), Deficit irrigation 80% of full irrigation for all growth stages DI80, Deficit irrigation 80% of full irrigation for both stages (tuber filling and maturity) DI80TF, Deficit Irrigation 70% of full irrigation for all growth stages DI70 , Deficit irrigation treatment 70% of full irrigation for the two stages (tuber filling and maturity) DI70TF.The results showed that there were no significant differences in productivity between the treatment 100% of full irrigation and two treatments of Deficit irrigation treatments 80% and 70% of full irrigation for the two stages (tuber filling and maturity) and the values was (32.72, 30.86, 30.74 Ton.h-3 respectively). While the results showed that there were significant differences in productivity between the treatment 100% of full irrigation, and each of the two treatments Deficit irrigation 80% of full irrigation for all stages of growth (DI80) and the treatment of Deficit irrigation 70% of full irrigation for all stages of growth (DI70), with a percentage decrease of 38% and 47%, respectively. The highest value of water use efficiency was recorded in Deficit irrigation treatment 70% of full irrigation for the two stages (tuber filling and maturity) DI70TF, with a value of 5.59 Kg.m-3, and it was followed by the treatment Deficit irrigation 80% of full irrigation for both stages (tuber filling and maturity) DI80TF with a value of 5.22 Kg.m-3. While the value of water use efficiency in the full irrigation treatment was 4.86 Kg.m-3. Where the treatments Deficit irrigation 80 and 70 % of full irrigation for both stages (tuber filling and maturity) saved the amount of irrigation water with values of (821, 1236 m3.h-1 respectively). As the results show that the success of implementing Deficit irrigation on the potato crop (Everest variety) requires not apply it in the early stages of growth, and that the optimal period of apply it extends during the growth and filling of tubers until the end of the maturity stage. with confirmation on the importance of using one of the two methods of Deficit irrigation 80% of full irrigation for the two stages of tuber filling and maturity DI80TF, and Deficit irrigation 70% of full irrigation for the two stages of filling tubers and maturity DI70TF.
Keywords: Deficit Irrigation; Potatoes; Water use efficiency; Productivity